Epoxy-Based/BaMnO4 Nanodielectrics: Dielectric Response and Energy Storage Efficiency - Despoina I. Batsouli (MDPI AG, 2021)
Compact capacitive energy storing/harvesting systems could play a key role in the urgent need for more energy-efficient technologies to address both energy and environmental issues. Therein, the purpose of the present work is to develop and investigate epoxy/BaMnO4 nanocomposites at various filler concentrations, which could be applicable as compact materials systems for energy storage and harvesting. Broadband dielectric spectroscopy was used for studying the dielectric properties and the relaxation processes of the examined nanodielectrics. The energy storing/retrieving ability of the nanocomposites was also evaluated via DC charge–discharge experiments. The coefficient of energy efficiency (neff) was found for all prepared nanocomposites to evaluate the energy performance of the systems. Dielectric data divulge the existence of two matrix-related relaxations, i.e., α-mode and β-mode, attributed to the glass-to-rubber transition of the polymer matrix and re-orientation of polar side groups, respectively. Interfacial polarization was also identified in the low-frequency and high-temperature region. The 7 phr BaMnO4 nanocomposite exhibits the best performance in terms of the stored and harvested energies compared to all systems. On the other hand, the 5 phr, 3 phr and 1 phr nanocomposites display optimum energy performance, reaching high values of neff.